Identification of genes associated with cortical malformation using a transposon-mediated somatic mutagenesis screen in mice - I-Ling Lu (Nature Portfolio, 2018)
Cortical malformations have a variety of causes. Here the authors use transposon mutagenesis to insert mutations into neural stem cells in the developing mouse cortex to screen for new candidate genes for cortical malformation, and validate some targets in human brain tissue.